The Effect of Problem Based Learning Model Assisted by Edunum Application on Numeracy Skills - Hidayatullah, Syarif; Masi, La; Misu, La; Salim (Jurnal Amal Pendidikan, 2024)
The purpose of this study was to determine the effect of Problem Based Learning model assisted by EduNum application on students' numeracy skills at SMAN 4 Kendari. The method in this study used Quantitative and Quasi Experiment type of research with Post-Test Only Control Grub Design research design. The results showed that there was an effect of Problem Based Learning model assisted by EduNum application on students' numeracy skills at SMAN 4 Kendari. This is based on the results of descriptive analysis for the numeracy skills of students in the class using the Problem Based Learning learning model assisted by EduNum application has an average of 81.11 with a percentage of 50% high ability category, 43.33% medium ability category and 6.67% low ability category while the class using the Problem Based Learning learning model without the help of EduNum application has an average of 71.39 with a percentage of 26.67% high ability category, 53.33% medium ability category and 20% low ability category. The results of inferential statistical analysis (independent test) obtained significant greater than 0.05 which means that there is an effect of Problem Based Learning learning model assisted by EduNum application on the numeracy skills of students at SMAN 4 Kendari.